Kesejahteraan Karyawan sebagai Pilar Produktivitas: Tinjauan Praktik HRD dalam Dunia Kerja - Zahra, Riska Akila (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In the modern work era, employee welfare is one of the crucial factors in creating a productive, healthy and sustainable work environment. This research aims to examine the contribution of Human Resource Development (HRD) practices to employee welfare and its impact on work productivity. The method used is descriptive qualitative with a case study approach, based on the author’s internship experience in the Human Resource Department of GranDhika Setiabudi Hotel Medan. Data was collected through participatory observation and documentation during the internship period. The results showed that the role of HR is not only limited to administrative functions, but also plays a strategic role in building holistic employee welfare. The findings during the internship at Hotel GranDhika Setiabudi Medan reinforce the view that employee well-being has a meaningful contribution to organizational productivity and sustainability. Therefore, optimizing the role of HR in the welfare aspect needs to be continuously developed through adaptive and sustainable policies and practices.